Ovarian Tumour in a Child with Vaginal Bleeding: A Rare Case Report - Amit Kumar; Sambedna; Rashi; Amit Kumar Sinha; Bindey Kumar (Journal of Clinical and Diagnostic Research, 2019)
Gynaecological malignancy account for 2% of all kinds of cancer in children and 60-70% of these lesions arise from ovaries. The clinical manifestations and histological types of ovarian tumours in paediatric population are different from those seen in adults. In pre menarche group usually ovarian tumours are of germ cell origin. These germ cell tumours in paediatric age group may present with features of precocious puberty. We report a case of ovarian tumour that presented with features of isosexual precocious puberty in the form of vaginal bleeding, in a four-year-old female child. She underwent surgical exploration and removal of the tumour with an attempt to preserve the reproductive function. She was relieved of the symptoms followed by the tumour removal as evidenced by the regular follow-ups.